2016
DOI: 10.1186/s12876-015-0415-y
|View full text |Cite
|
Sign up to set email alerts
|

Risks of hospitalization and drug consumption in children and young adults with diagnosed celiac disease and the role of maternal education: a population-based matched birth cohort study

Abstract: BackgroundCeliac disease (CD) may affect healthcare use in children and young adults. Socio-economic factors may act as a confounder or effect modifier. We assessed such hypotheses in a population-based birth cohort of young celiac subjects and references matched by maternal education.MethodsThe cohort included all newborns recorded in the Medical Birth Register of Friuli-Venezia Giulia Region (Italy) between 1989 and 2011. CD incident cases were identified through pathology reports, hospital discharges and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…Previous reports on the more severe progression of chronic ALD and challenges of stopping alcohol abuse in females have been documented previously, suggesting that women are more susceptible to alcohol-related liver disease [41]. One recent study showed that light drinking in females does not produce any significant elevation in ALT or liver injury [42], consistent with the studies in males. Another study on hepatic encephalopathy showed that increased risk for the condition was associated with female sex [43].…”
Section: Sex Differences In Alcohol Pharmacologysupporting
confidence: 76%
“…Previous reports on the more severe progression of chronic ALD and challenges of stopping alcohol abuse in females have been documented previously, suggesting that women are more susceptible to alcohol-related liver disease [41]. One recent study showed that light drinking in females does not produce any significant elevation in ALT or liver injury [42], consistent with the studies in males. Another study on hepatic encephalopathy showed that increased risk for the condition was associated with female sex [43].…”
Section: Sex Differences In Alcohol Pharmacologysupporting
confidence: 76%
“…YHS patients generally experience liver disease13141516171819202122 as a direct result of disordered liver metabolism. From the histopathological observations, a significant change in the microscopic histology of H&E stained liver sections was detected in the YHS group.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review and meta-analysis showed that current smokers with CD were at increased risk of intestinal resection compared to never smokers (HR 1.27, 95% CI 1.08 to 1.49); however, there was no difference in the need for surgery when former and never smokers were compared (HR 1.11, 95% CI 0.95 to 1.30) [ 187 ]. Another meta-analysis of 33 studies revealed that as compared to non-smokers, smokers had increased odds of flare of disease activity (OR 1.56; 95% CI 1.21–2.01), flare after surgery (OR 1.97; 95% CI 1.36–2.85), need for first surgery (OR 1.68; 95% CI 1.33–2.12), and need for second surgery (OR 2.17; 95% CI 1.63–2.89), and quitting smoking was found to ameliorate this [ 188 ].…”
Section: The Asian Working Group Guidelines Regarding Diet In Inflammmentioning
confidence: 99%